PUBLIC SPEAKING MASTERY FOR SMK GRADUATES’ COMMUNICATION SKILLS: Penguasaan public speaking untuk mendukung kemampuan komunikasi lulusan SMK - Ambalegin Ambalegin; Afriana Afriana; Angel Purwanti; Tomi Arianto; Nurma Dhona Handayani (PUAN INDONESIA, 2023)
The aim of this training was to acknowledge the SMK students the skills of communication. Public speaking was the main topic of this training. Public speaking mastery affects people’s relationship, leadership, and attitudes. The SMK graduates must have public speaking skill for their future when they are welcomed in workplace. The collaboration of the vocational skills, public speaking skill, and English-speaking skill will enter the graduates to the successful future. This training was held at SMKN 7 Batam from November 10th to 11th, 2022 with MM, RPL, TKJ, TITL, and TJAT students as the participants. This activity applied the community education with training-course technique. The training included mentoring, discussion, and practice in which the materials were the strategies of public speaking and basic course of English. The result of the activity was the educating the participants in controlling fear and anxiety while speaking in public. Besides, it was increasing the participants’ confidence.